Present state and prospects of agricultural development of Ukraine - Shyshkin, Viktor; Onyshchenko, Oksana (Management and Entrepreneurship: Trends of Development, 2020)
The article analyses the current state, major product groups and foreign markets of Ukrainian agricultural products. In addition, the potential for development of Ukraine’s agro-industrial complex are outlined. The aim of the article is to assess the current state of affairs, to determine the existing and hidden potential, the main trends and obstacles to the disclosure of the export potential of agricultural products in Ukraine. As a result, the main measures to eliminate obstacles to unleash the export potential of the Ukrainian agro-industrial complex are proposed. The findings of the study also prove that the agrarian sector remains an important part of the Ukrainian economy, providing a significant share of foreign exchange earnings. The main driver of growth in agricultural production in Ukraine remains an increase in crop yields due to precision farming, new hybrids, etc. It is stated that the opening of new markets and niches will allow Ukrainian agricultural exporters to consolidate their positions in the international arena. JEL Classification: Q11, Q18